Remediation of the oil palm frond juice base medium via efficient pretreatment and dilution factor strategy for bacterial cellulose production yield enhancement - Mohamad, Shahril; Abdullah, Luqman Chuah; Jamari, Saidatul Shima; Sy Mohamad, Sharifah Fathiyah (Elsevier, 2025)
The presence of inhibitory components, especially lignin and weak acids in oil palm frond juice medium detrimentally affects bacterial cellulose production yield. This study investigated a two-stage pre-treatment and dilution strategy to enhance the suitability of oil palm frond juice. Pre-treatments for lignin removal included alkaline precipitation with 0.025 M sodium hydroxide, which reduced the lignin content by 73.5 %, and activated carbon adsorption at 6 % w/v, which achieve over 95.1 % lignin removal. Additional treatment procedure using dilution factors effectively mitigated the adverse effects of both pretreatment, including chemical residues, pH instability, and volume loss. Bacterial cellulose production in pre-treated oil palm frond juice with 40 % water dilution yielded at 2.35 g/L from alkaline pretreated medium and 2.57 g/L from activated carbon adsorption pretreated medium, representing a 7.0-fold and 3.6-fold increase over undiluted and untreated samples, respectively. These results demonstrate the effectiveness of lignin removal using alkaline precipitation or activated carbon adsorption with a dilution factor significantly improves the viability of oil palm frond juice as a high-yield bacterial cellulose production medium.